Junctional Bradycardia as Early Sign of Digoxin Toxicity in a Premature Infant with Congestive Heart Failure due to a Left to Right Shunt - Soham Dasgupta; Ashraf M. Aly; Sunil K. Jain (Thieme Medical Publishers, Inc., 2016)
Abstract Introduction Congestive heart failure due to left to right cardiac shunt is usually managed medically with diuretics, angiotensin converting enzyme inhibitors, and, in some cases, with the addition of digoxin. Case We report a 31-week gestation premature male infant who did not respond to such treatment and developed hyperaldosteronism and severe hypokalemia secondary to activation of the renin angiotensin aldosterone system. The hypokalemia was not responsive to intravenous KCL supplementation and induced digoxin toxicity despite a relatively normal digoxin level. The earliest signs of digoxin toxicity in the patient were junctional rhythm and bradycardia. The discontinuation of digoxin and the administration of digoxin specific immunoglobulin fragments (Fab) reversed those changes. The addition of spironolactone (an aldosterone antagonist) had a dramatic effect, resulting in clinical improvement of the patient coupled with normalization of Q4 serum and urine electrolytes. Conclusion Serum Digoxin level alone may fail as an independent guide in the diagnosis of digoxin toxicity when hypokalemia is present. In premature infants with congestive heart failure and hypokalemia, addition of an aldosterone antagonist should be considered.